Pengembangan Aplikasi Visualisasi E-Catalog Furniture Menggunakan Teknologi Realitas Tertambah Berbasis Android - Tegar Setiawan; Alexander Waworuntu (UNIVERSITAS KALBIS, 2022)
This research aims to make it easier for people who want to purchase furniture without visiting a store to see the product in person. The solution is an investment in Markerless Augmented Reality technology that will provide them with convenience. The Multimedia Development Life Cycle method is the answer to many successful methods that can simplify the application development process. This study employs Unity software and Vuforia devices.. Smartphone devices themselves must use Android because the use of Android-based smartphones is still high around us and easily found so that the target of this application becomes easier to implement on the platform. The results of creating an application are files that are converted into .Apk extensions. In this application there are also features that bring up an information text related to the details of one of the furniture objects that appear in the real world.